Relationship Between Teacher Motivation And Student Learning Outcomes In High School - Wuisang, Jerry RH; Hutahaean, Lidia Aprileny; Afnita, Vinda (LPPM Universitas PGRI Sumatera Barat, 2024)
This study aims to determine The Relationship Between Teacher Motivation and Student Learning Outcomes at Sma Negeri 1 Tondano. The method used in the correlational approach research is descriptive research which is often used to achieve the relationship between several variables. Correlation studies allow researchers to meet how much the variables are related to each other. The population of this study was all students of class XI in Economics at SMA Negeri 1 Tondano totaling 64 students. The sample of this study was half of the class XI students totaling 64 students, namely 32 students. The research was conducted at SMA Negeri 1 Tondano. The research was conducted for two months. Based on the Collection, Processing and Analysis of Data (Research Results) it can be concluded as follows: Providing external motivation in this case teachers is very helpful in the development of learning quality and student learning outcomes at SMA Negeri 1 Tondano. A good relationship between teachers and students greatly influences motivation and encouragement in student success both at school, in society, and in the family environment. The test results that obtained a Correlation Coefficient of 0.72 clearly illustrate how important teacher motivation is in order to improve student learning outcomes at SMA Negeri 1 Tondano.